Prenatal chromosomal microarray analysis: a survey of prenatal genetic counselors' experiences and attitudes. (1st March 2013) - Mikhaelian, Marina; Veach, Patricia McCarthy; MacFarlane, Ian; LeRoy, Bonnie S.; Bower, Matthew
ABSTRACT Objective Studies showing the efficacy and accuracy of chromosomal microarray analysis (CMA) in prenatal diagnosis may position it as a first‐tier prenatal test. This study seeks to characterize the practices and attitudes of North American prenatal genetic counselors regarding CMA. Method Genetic counselors (N = 196) in Canada and the USA responded to an anonymous online survey. Completed surveys were analyzed (n = 160). Results Most respondents viewed CMA as useful (73%), presented CMA to patients (84%), and had ordered CMA at least once (69%). The use of full versus targeted arrays varied. Logistic regression analyses identified three significant predictors for the view that prenatal CMA is useful: more prenatal counseling experience, younger age, and previously presenting CMA to a patient. Three factors predicted the likelihood of offering CMA to prenatal patients: percentage of time spent in prenatal practice, belief that CMA is useful, and practicing in the USA (versus Canada). Reasons cited for not using CMA included financial concerns, the possibility of ambiguous results, and ethical concerns. Most respondents (n = 111) believed that ambiguous results are an ethical issue. Conclusion Clinical guidelines for prenatal CMA, further research on specific copy number variants, and broader availability of targeted arrays to reduce ambiguous results are needed. © 2013 John Wiley & Sons, Ltd.